The School Principal’s Strategies in Maintaining the Quality of Education at Muhammadiyah 1 High School Palembang - Kanada, Rabial; Firmansyah; Zulkipli (International Journal of Applied Educational Research (IJAER), 2024)
High quality education is a significant priority in efforts to enhance students' competencies and maintain the school's reputation. This research aims to uncover the strategies of the school principal in maintaining the quality of education at Senior High School Muhammadiyah 1 Palembang. The study utilizes a qualitative method with a case study approach, conducting in-depth interviews with the school principal, teachers, and staff, as well as non-systematic observations of school activities, and relevant documentation studies. After data collection, thematic analysis was employed, involving data coding, identification of main themes, and interpretation of findings within the context of the school principal's strategies to uphold the quality of education. The research findings indicate that the principal of Senior High School Muhammadiyah 1 Palembang demonstrates a strong commitment to enhancing the quality of education through various strategies including teacher development, development of a curriculum based on local values, empowerment of students in soft skills development, close collaboration with parents and the community, and utilization of technology in learning. Senior High School Muhammadiyah 1 Palembang also engages in partnerships with private companies and alumni to support educational programs, and the formation of the school quality team plays a crucial role in monitoring and evaluating education. All these efforts create an educational environment focused on sustainable quality and student-oriented needs.